Introduction to Science Learning Tools Based on Waste for Elementary School Students - Ekawita, Riska; Supiyati; Saputra, Rahmat; Yosia Pandu S; Melisa, Wery; Yuliza, Elfi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Regulations and laws in Indonesia strongly support learning using teaching aids. Teaching media or aids are essential in the process of knowledge transfer for students. Students will find it easier to understand the lesson material if assisted by teaching aids, even if they are in a simple form. Teachers can introduce teaching aids made from recycled waste materials. Therefore, the aim of this community service activity is to introduce the development of teaching materials made from waste materials. A community service activity utilizing waste materials (cardboard, sticks, etc.) as classroom learning media will be conducted at SDIT Nurul Fikri, Bengkulu City. The target audience for this community service activity is teachers and some students. The method used consists of theory and practice. The service team will train teachers and students to create science teaching aids, particularly on the themes of pressure and energy. As a result of this activity, several examples of science teaching aids made from waste materials were produced. These teaching aids will certainly help enhance students' understanding and create their own appeal toward science subjects.